A high-efficiency dust suppressant for preventing and controlling construction dust pollution and preparation method thereof
By using raw materials such as polyacrylamide, sodium lignin sulfonate and pectin, high-efficiency dust inhibitors prepared by graft copolymerization, the problem of difficult degradation and insufficient consolidation strength of existing dust inhibitors is solved, and the effect of effectively consolidating dust and extending dust suppression time is achieved.
Patent Information
- Application Number
- CN202410748008.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-11
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-06-11
AI Technical Summary
Existing chemical dust inhibitors are difficult to degrade and have insufficient consolidation strength, so they cannot effectively prevent and control building dust pollution.
Polyacrylamide, sodium lignin sulfonate and pectin are used as the main raw materials to prepare high-efficiency dust inhibitors through graft copolymerization, and water retention agents and surfactants are added to improve dust inhibition effects.
The prepared dust inhibitor has good adhesion and consolidation strength, can effectively consolidate dust, extend dust suppression time, reduce the risk of secondary dust, and is environmentally friendly and degradable.
Smart Images

Figure CN118667085B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dust suppressant preparation, in particular to a high-efficiency dust suppressant for preventing and controlling construction dust pollution and a preparation method thereof. Background Art
[0002] As countries pay more attention to the environment, environmental pollution has become one of the focuses of global attention. Among them, air pollution is closely related to human life and has become a major global environmental problem. Human production activities are usually accompanied by the generation of dust. The dust generated by construction activities is called "construction dust", which accounts for more than 40% of the total suspended particulate matter and is one of the main pollutants in the atmosphere. A large amount of dust generated at the construction site will spread to the surrounding environment, seriously affecting the air quality of the surrounding environment and causing severe weather such as haze. The life and health of construction workers on site are seriously threatened due to long-term exposure to high-concentration dust environments. They are prone to pneumoconiosis, lung cancer and cardiovascular and cerebrovascular diseases, among which the incidence of diseases such as pulmonary fibrosis and respiratory infections exceeds 25%. The impact of construction dust on health varies greatly depending on the source of construction dust. The main hazard factor in construction dust is silica, but in addition, the heavy metal elements contained in dust cannot be ignored. Although there are many research results on dust, most of them are concentrated in the fields of coal dust, road dust, factory dust, etc., while there are relatively few studies on construction dust.
[0003] At present, the commonly used dust suppression methods include water sprinkling and chemical dust suppression. Water sprinkling achieves dust suppression by wetting the dust surface and reducing dust. It has the advantages of simple operation and low price, so it is widely used. However, the duration of water sprinkling is short, and the rapid evaporation of water leads to poor dust removal effect. When faced with more complex environmental conditions, the dust suppression effect is even more limited, and repeated spraying is required, which not only causes a waste of water resources, but also requires certain manpower and material resources, which increases the cost of dust suppression to a certain extent. Chemical dust suppression has the advantages of significant dust suppression effect and water resource saving, and is the mainstream direction of current development. Although chemical dust suppression has achieved many research results, some chemical dust suppressants still have defects such as difficult degradation and low consolidation strength. Therefore, it is of great significance to develop a dust suppressant that has a significant dust suppression effect and is environmentally friendly for the prevention and control of construction dust pollution. Summary of the invention
[0004] In view of the deficiencies in the prior art and to solve the defects of traditional chemical dust suppressants such as difficulty in degradation and low consolidation strength, the present invention provides a high-efficiency dust suppressant for preventing and controlling construction dust pollution and a preparation method thereof.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A high-efficiency dust suppressant for preventing and controlling construction dust pollution comprises the following raw materials in proportion by weight: 0.5%-1.0% polyacrylamide, 0.15%-0.30% pectin, 0.15%-0.30% sodium lignin sulfonate, 0.05%-0.15% initiator, 0.05%-0.10% cross-linking agent, 0.25%-2.5% water retaining agent, 0.125%-1.125% surfactant, and the balance is water.
[0007] Furthermore, the initiator is potassium persulfate.
[0008] Furthermore, the cross-linking agent is N, N'-methylenebisacrylamide.
[0009] Furthermore, the water retaining agent is carboxymethyl chitosan.
[0010] Furthermore, the surfactant is 3-sulfopropyltetradecyl dimethyl betaine.
[0011] The second aspect of the present invention provides a method for preparing a high-efficiency dust suppressant for preventing and controlling construction dust pollution, comprising the following steps:
[0012] S1: Place pectin, sodium lignin sulfonate and water in a beaker and heat and stir to fully dissolve the pectin and sodium lignin sulfonate.
[0013] S2: Add an initiator, a crosslinking agent and polyacrylamide to the solution prepared in S1, continue heating and stirring, and carry out a grafting reaction.
[0014] S3: Cool the solution prepared in S2 at room temperature.
[0015] S4: Add a water retaining agent and a surfactant to the cooled solution in S3, stir, and mix well to obtain a high-efficiency dust suppressant solution.
[0016] S5: Bottle the high-efficiency dust suppressant solution prepared in S4 for storage.
[0017] Furthermore, the stirring temperature in S1 is 40-50° C., and the stirring is performed until the pectin and sodium lignin sulfonate are fully dissolved.
[0018] Furthermore, the grafting reaction temperature in S2 is 60-80° C., and the grafting time is 1-2 h.
[0019] Furthermore, the cooling time in S3 is 2.5 to 3.5 hours.
[0020] The beneficial effects of the present invention are:
[0021] The present invention provides a high-efficiency dust suppressant for preventing and controlling construction dust pollution and a preparation method thereof. Polyacrylamide, sodium lignin sulfonate and pectin are selected as main raw materials and prepared by graft copolymerization. The raw materials used are widely available, low in price, and simple in preparation conditions. At the same time, the grafted materials sodium lignin sulfonate and pectin are both green materials, environmentally friendly and degradable, which improves the degradability of the dust suppressant. In addition, the dust suppressant of the present invention has good adhesion, can form a dust suppression film on the surface of dust, has the function of consolidating dust, so that the dust has a certain consolidation strength, and resists strong wind erosion, thereby effectively preventing the dust from being broken and forming secondary dust. By adding a water-retaining agent and a surfactant, the water-retaining property and wetting property of the dust suppressant are further improved, the dust suppression time of the dust suppressant is effectively extended, the consolidation strength of the dust is improved, and the dust suppressant has a better dust suppression effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is a preparation flow chart of the present invention;
[0023] Figure 2 It is the preparation mechanism diagram of the present invention;
[0024] Figure 3 This is the infrared spectrum of the grafted product prepared in Example 1 of the present invention;
[0025] Figure 4 The scanning electron microscope images of dust samples under different conditions of the present invention, wherein (a) is a dust sample treated with clean water, (b) is a dust sample treated with a comparative example, and (c) is a dust sample treated with Example 1;
[0026] Figure 5 This is a graph showing the mass loss rate of the dust pile under different conditions of the present invention. DETAILED DESCRIPTION
[0027] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0028] Preparation process of high efficiency dust suppressant
[0029] (1) Dissolution of pectin and sodium lignin sulfonate
[0030] Weigh a certain amount of pectin and sodium lignin sulfonate according to weight, place them in the same beaker, add a certain amount of deionized water, then place the beaker in a magnetic stirring pot for heating and stirring at a temperature of 40-50°C until the pectin and sodium lignin sulfonate are completely dissolved.
[0031] (2) Grafting reaction
[0032] A certain amount of initiator, crosslinker and polyacrylamide were added to the beaker containing dissolved pectin and sodium lignin sulfonate, and then the beaker was placed in a magnetic stirring pot for heating and stirring, and the heating temperature was set to 60-80°C. After a period of grafting, the grafted product was taken out and placed at room temperature for cooling to obtain a grafted product.
[0033] (3) Preparation of high-efficiency dust suppressants
[0034] Add a certain amount of water retaining agent and surfactant to the cooled solution, stir and mix well to obtain a high-efficiency dust suppressant solution.
[0035] Preparation mechanism of high efficiency dust suppressant
[0036] Figure 2 The synthesis mechanism of the high-efficiency dust suppressant is demonstrated. Lignosulfonic acid and pectin contain numerous hydroxyl functional groups. Under the action of the initiator potassium persulfate, they will lose hydrogen atoms and generate active sites. At the same time, the methylene functional groups on the polyacrylamide molecular chain will also form active centers under the attack of potassium persulfate, and combine with the active sites formed on sodium lignin sulfonate and pectin to form more stable ether bonds, so that sodium lignin sulfonate and pectin are grafted onto the polyacrylamide molecular chain. The crosslinking agent N, N'-methylenebisacrylamide will also form active sites under the action of potassium persulfate, and combine with the active centers on the polyacrylamide molecular chain to crosslink two polyacrylamide molecular chains together. Under the action of many N, N'-methylenebisacrylamide molecules, different polyacrylamide molecular chains are crosslinked with each other, gradually forming a more complex network structure, and a grafted product is obtained. The surfactant 3-sulfopropyl tetradecyl dimethyl betaine and the water-retaining agent carboxymethyl chitosan are mixed into the grafted product and evenly dispersed in the solution to form a high-efficiency dust suppressant.
[0037] This will be described below with reference to specific embodiments.
[0038] Embodiment 1:
[0039] The steps of preparing a high-efficiency dust suppressant for preventing and controlling construction dust pollution proposed by the present invention are as follows:
[0040] S1: 0.3 g pectin, 0.3 g sodium lignin sulfonate and 150 ml water were placed in a beaker, and heated and stirred at 45° C. to fully dissolve the pectin and sodium lignin sulfonate.
[0041] S2: Add 0.2 g potassium persulfate, 0.15 g N, N'-methylenebisacrylamide and 1 g polyacrylamide to the solution prepared in S1, continue heating and stirring at 70°C to carry out grafting reaction, and the reaction time is 1.5 h.
[0042] S3: Cool the solution prepared in S2 at room temperature for 3 hours.
[0043] S4: Add 0.75 g of carboxymethyl chitosan and 0.3 g of 3-sulfopropyltetradecyl dimethyl betaine to the cooled solution in S3, and stir to obtain a high-efficiency dust suppressant solution.
[0044] In order to better verify the implementation effect of the present invention, the solution obtained after cooling S3 in Example 1 is used as a comparative example.
[0045] Test Example 1: Infrared spectroscopy experiment
[0046] The grafted product prepared in Example 1 was dried and ground to obtain a grafted product powder, and then an infrared spectrum experiment was performed. The spectrum of polyacrylamide was used as a reference to observe the changes in the types and contents of functional groups of polyacrylamide and the grafted product, and to study the grafting conditions of each component. The test results are as follows: Figure 3 The absorption peak positions and corresponding functional group types are shown in Table 1.
[0047] Table 1 Main absorption peaks and functional groups of polyacrylamide and grafted products
[0048]
[0049] At 3500-3100cm -1 The grafted product has a sharper absorption peak at 3500-3100cm. This is because there is only -NH functional group in polyacrylamide, while there is -OH functional group in the grafted product. This is related to the hydroxyl groups contained in sodium lignin sulfonate and pectin. The superposition of -NH and -OH functional groups makes the grafted product have a sharper absorption peak at 3500-3100cm. -1 The absorption peak at 1120cm -1 、1040cm -1 、690cm -1 There are three unique absorption peaks in the grafted product, which is because sodium lignin sulfonate contains sulfonic acid groups -HSO 3 , so that the grafted product at 1120cm -1 There is an absorption peak at 1040cm -1 The absorption peak at 690cm corresponds to the -CO functional group in the hydroxyl group, which is related to the hydroxyl groups contained in sodium lignin sulfonate and pectin. -1 The absorption peak of substituted benzene is at 40°, which is related to the benzene ring contained in sodium lignin sulfonate. The above results show that sodium lignin sulfonate and pectin have been successfully grafted onto the molecular chain of polyacrylamide.
[0050] Test Example 2: Scanning Electron Microscope Experiment
[0051] The dust sample was treated with the high-efficiency dust suppressant prepared in Example 1, and the dust sample was treated with clean water and the dust suppressant prepared in the comparative example as a control. The microscopic morphology of the dust sample surface was obtained by scanning electron microscopy experiment, and the changes of the dust surface under different conditions were compared. The results are as follows: Figure 4 As shown. From the electron microscope image magnified to 500 times, it can be seen that the dust samples treated with water have loosely distributed dust particles and small particles. After magnification to 2000 times, only small dust particles can be seen. This is because the consolidation performance of water is limited. After the dust samples treated with water are dried, the evaporation of water causes the consolidation performance to be greatly reduced, and the dust particles are broken and smaller again. The dust treated in Example 1 and the comparative example is arranged more tightly. When observed under 2000 times, it is found that many small dust particles are bonded to form large dust particles. This is because both Example 1 and the comparative example have a high viscosity, can effectively adsorb dust particles, and can still provide a certain consolidation strength after drying to prevent dust particles from breaking. Compared with the comparative example, the dust particles treated in Example 1 are larger and more tightly bonded, indicating that its viscosity is higher and the consolidation strength provided is greater.
[0052] Test Example 3: Anti-wind erosion test
[0053] The high-efficiency dust suppressant prepared in Example 1 was used to treat the dust sample, and the dust sample treated with clean water and the dust suppressant prepared in the comparative example was used as a control. The dust suppression performance of the high-efficiency dust suppressant was compared and analyzed through the wind erosion resistance test. In the experiment, three 20cm×20cm glass plates were prepared, and 20g of dry dust was allowed to fall naturally on the glass plates to form a dust pile. Then, equal amounts of clean water, and the dust suppressant solution prepared in Example 1 and the comparative example were sprayed on the dust pile to wet the dust surface. The treated dust sample was placed in an oven at 60°C and dried for 6 hours, then taken out and the dust weight M at this time was weighed. 0 Place the dust pile in front of the fan for blowing, and measure the residual mass M every 10 minutes. x , the mass loss rate of the dust pile is calculated by formula (1). The wind speed of the fan is set to 4m / s, 8m / s, 12m / s, and 16m / s.
[0054] (1)
[0055] Where MLR is the mass loss rate of dust pile, %;
[0056] M 0 ——initial mass of dust pile, g;
[0057] M x ——Mass of dust pile after wind erosion, g;
[0058] Through the wind erosion test, the mass loss rate of dust pile was obtained over time, such as Figure 5 As shown in Table 2, after the wind erosion experiment, the maximum mass loss rate of the dust pile under different conditions is shown in Table 2. When the wind speed is 4m / s, the mass loss rate of the dust pile is relatively low. The mass of the dust pile treated in Example 1 and the comparative example no longer changes after a period of time, while the dust pile treated with water maintains a certain speed of mass loss. With the increase of wind speed, the mass lost by the dust pile treated with water within 30min also gradually increases. When the wind speed reaches 12m / s, the maximum mass loss rate exceeds 90%. When the wind speed of the dust pile treated with the comparative example is 4-12m / s, the mass change range is not large, but when the wind speed reaches 16m / s, the mass begins to fluctuate greatly. This is because the comparative example forms a dust suppression film on the surface of the dust pile, which can effectively adsorb and consolidate dust, making the surface of the dust pile not easily damaged and cracked, reducing the generation of secondary dust. However, with the increase of wind speed, the surface of the dust pile treated with the comparative example is gradually eroded, the protective effect of the dust suppression film is destroyed, and the dust inside begins to be exposed to strong winds. However, the internal structure of the dust pile is still relatively loose and easily blown away by strong winds, resulting in a sudden increase in the dust mass loss rate. Example 1 has stronger permeability and can penetrate into the dust pile to consolidate the dust, so that the dust treated by Example 1 has a higher degree of consolidation, and can still effectively reduce the mass loss of dust even in a strong wind of 16m / s. In summary, the high-efficiency dust suppressant prepared by the present invention has excellent dust suppression performance, can effectively consolidate dust, and reduce the generation of dust.
[0059] Table 2 Maximum mass loss rate of dust pile at different wind speeds
[0060]
[0061] Embodiment 2:
[0062] The initiator content added to S2 in Example 1 was adjusted to 0.1g and 0.3g respectively. The stirring temperature in S1 was 50°C, the grafting reaction temperature in S2 was 60°C, and the cooling time in S3 was 3h to obtain a high-efficiency dust suppressant solution. The viscosity of the prepared dust suppressant solution was tested by a viscometer. After testing, when the amount of initiator added was 0.1g, the viscosity of the dust suppressant solution was 24.2mPa s, when the amount of initiator added is 0.3g, the viscosity of the dust suppressant solution is 30.5mPa s.
[0063] Embodiment 3:
[0064] The content of crosslinking agent added to S2 in Example 1 was adjusted to 0.1g and 0.2g respectively. The stirring temperature in S1 was 40°C, the grafting reaction temperature in S2 was 80°C, and the cooling time in S3 was 3h to obtain a high-efficiency dust suppressant solution. The viscosity of the prepared dust suppressant solution was tested by a viscometer. After testing, when the amount of crosslinking agent added was 0.1g, the viscosity of the dust suppressant solution was 29.9mPa s, when the amount of cross-linking agent added is 0.2g, the viscosity of the dust suppressant solution is 31.1mPa s.
[0065] Embodiment 4:
[0066] The water retaining agent content added to S4 in Example 1 was adjusted to 0.5g and 1.0g respectively. The preparation process was the same as that in Example 1. The prepared dust suppressant solution was sprayed on dust samples of equal mass, and then the samples were placed in an oven at 60°C for 2 hours. After testing, when the amount of water retaining agent added was 0.5g, the water retention rate of the dust sample was 41.3%, and when the amount of water retaining agent added was 1.0g, the water retention rate of the dust sample was 44.1%.
[0067] Embodiment 5:
[0068] The surfactant content of S4 added in Example 1 was adjusted to 0.2 g and 0.4 g, respectively. The preparation process was the same as that in Example 1. The surface tension of the prepared dust suppressant solution was tested by a surface tension meter. After testing, when the amount of surfactant added was 0.2 g, the viscosity of the dust suppressant solution was 37.85 N / m, and when the amount of surfactant added was 0.4 g, the viscosity of the dust suppressant solution was 37.53 N / m.
[0069] Therefore, the high-efficiency dust suppressant for preventing and controlling construction dust pollution prepared by the present invention has certain bonding properties, can effectively consolidate dust particles, and provide good consolidation strength for dust piles, so that dust piles are not easily damaged by wind erosion, resulting in secondary dust pollution. At the same time, the high-efficiency dust suppressant has a low surface tension, can effectively wet the dust surface, and penetrate into the dust to improve the overall consolidation strength of the dust. Good water retention properties enable the high-efficiency dust suppressant to delay water evaporation, thereby greatly improving the dust suppression time, so that the high-efficiency dust suppressant has a better and more lasting dust suppression effect.
[0070] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A high-efficiency dust suppressant for preventing and controlling construction dust pollution, characterized in that: The invention comprises the following raw materials in proportion by weight: 0.5% to 1.0% polyacrylamide, 0.15% to 0.30% pectin, 0.15% to 0.30% sodium lignin sulfonate, 0.05% to 0.15% initiator, 0.05% to 0.10% cross-linking agent, 0.25% to 2.5% water retaining agent, 0.125% to 1.125% surfactant, and the balance is water; the cross-linking agent is N, N'-methylenebisacrylamide, the water retaining agent is carboxymethyl chitosan, and the surfactant is 3-sulfopropyl tetradecyl dimethyl betaine.
2. The high-efficiency dust suppressant according to claim 1, characterized in that: The initiator is potassium persulfate.
3. The method for preparing a high-efficiency dust suppressant for preventing and controlling construction dust pollution according to claim 1 or 2, characterized in that: The following steps are involved: S1: Place pectin, sodium lignin sulfonate and water in a beaker and heat and stir to fully dissolve the pectin and sodium lignin sulfonate; S2: adding initiator, N, N'-methylenebisacrylamide and polyacrylamide to the solution prepared in S1, and continuing heating and stirring to carry out grafting reaction; S3: Cooling the solution prepared in S2 at room temperature; S4: adding carboxymethyl chitosan and 3-sulfopropyltetradecyl dimethyl betaine to the cooled solution in S3, stirring and mixing evenly to obtain a high-efficiency dust suppressant solution.
4. The preparation method according to claim 3, characterized in that: The stirring temperature in S1 is 40-50°C, and the stirring is performed until pectin and sodium lignin sulfonate are fully dissolved.
5. The preparation method according to claim 3, characterized in that: The grafting reaction temperature in S2 is 60~80℃, and the grafting time is 1~2h.
6. The preparation method according to claim 3, characterized in that: The cooling time in S3 is 2.5~3.5h.
Citation Information
Patent Citations
High-molecular coagulation cohesive dust suppression agent and preparation method thereof
CN108865070A
Antiviral soil-fixing dust suppressant as well as preparation method and application thereof
CN112111248A